PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PT. SUZUKI INDOMOBIL MOTOR - M. Zainal Aripin; Rasmansyah (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
This research was conducted based on the existence of problems in the competence and physical work environment of employee performance. This study aims to determine the effect of competencies and physical work environment simultaneously or partially on the performance of employees of PT. Suzuki Indomobil Motor. The sampling technique is the sample random sampling technique. The type of research used is descriptive and verivative research methods, with data collection techniques using primary data and secondary data. The results showed that competency, physical work environment, and performance were categorized quite well. Based on the calculation, it can be seen that simultaneously the competence and physical work environment have a positive and significant influence on the performance of the employees of PT. Suzuki Indomobil Motor. Partially shows that the physical work environment has the most dominant influence on the performance of employees of PT. Suzuki Indomobil Motor